A theoretical study of the spectroscopic properties of B2H6 and of a series of BxHyz− species (x = 1−12, y = 3−14, z = 0−2): From BH3 to B12H122−. (4th May 2016) - Sethio, Daniel; Lawson Daku, Latévi Max; Hagemann, Hans
Abstract: The characterization of boron-hydrogen compounds is an active research area which encompasses subjects as diverse as the chemistry and structures of closoboranes or the thermal decomposition mechanism of the borohydrides. Due to their high gravimetric hydrogen content, borohydrides are considered as potential hydrogen storage materials. Their thermal decompositions are multistep processes, for which the intermediate products are not easily identified. To help address this issue, we have extensively investigated the vibrational and NMR properties of 21 relevant B m H n z − boron-hydrogen species ( m = 1–12; n = 1–14; z = 0–2) within density functional theory. We could thus show that the B3LYP-D2 dispersion-corrected hybrid can be used in combination with the large cc-pVTZ basis set for the reliable prediction of the 11 B and 1 H NMR spectra of the boron-hydrogen species, and also for the reliable prediction of their IR and Raman spectra while taking into account the anharmonicity of their molecular vibrations. Graphical abstract: A very good correlation is observed between the (B3LYP-D2/cc-pVTZ)-calculated anharmonic and the experimental vibrational frequencies for a series of boron-hydrogen species. As illustrated here for B12 H 12 2 − whose parallel (red) and perpendicular (blue) polarized Raman spectra are shown, the evidenced correlation provides a reliable means of identifying intermediate decomposition products in the study of potential hydrogen storage. Highlights: Density functional theory is applied to the study of 21 boron-hydrogen species. Their 11 B and 1 H NMR spectra and also their IR and Raman spectra are reliably predicted at the B3LYP-D2/cc-pVTZ level. The inclusion of anharmonicity significantly improves the agreement between calculated and experimental vibrational frequencies.